The Application of Mediastinoscopy in the Differential Diagnosis and Preoperative Staging on Lung Cancer - Feng MAO; Liang ZHANG; Minghui CAI; Zhengping DING; Yang SHEN-TU (Chinese Journal of Lung Cancer, 2014)
Background and objective To discuss the clinical application of mediastinoscopy in the differential diagnosis and preoperative staging on lung cancer. Methods A total of 361 cases of patients were included in the study, of which 162 cases were undiagnosed mediastinal tumor patients before operation, and 199 patients were suspected or diagnosed with lung cancer or mediastinal lymph nodes enlargment(short diameter ≥1.0 cm). All patients underwent surgery, including 308 cases standard cervical mediastinoscopy (SCM) , 53 cases parasternal mediastinoscopy (PM). Results Taking pathology diagnosis as the gold standard, the mediastinoscopy diagnostic accuracy, sensitivity, specificity, positive predictive value, negative predictive value are 98.11%, 97.62%, 100%, 100%, 91.67% and 98.28%, 98.03%, a 100%, 100%, 100% to mediastinal masses and mediastinal lymph node metastasis of lung cancer. Total seven cases suffered from complications of surgery-related, the complication rate was 1.93 percent (P<0.05). Conclusion The trauma of the mediastinoscopy is slight, which is safe, reliable, able to take in sufficient tissue quantities. Mediastinoscopy is highly helpful not only in diagnostic of mediastinal mass, but also in the differential diagnosis of lung cancer, and it’s an important method and the gold standard of preoperative staging on lung cancer.